ChemInform Abstract: Mn(OAc)3‐Mediated Phosphonation—Lactonization of Alkenoic Acids: Synthesis of Phosphono‐γ‐butyrolactones. Issue 25 (5th June 2015) - Gao, Yuzhen; Li, Xueqin; Xu, Jian; Wu, Yile; Chen, Weizhu; Tang, Guo; Zhao, Yufen
Abstract: The reaction proceeds through Mn(OAc)3 ‐mediated radical oxidative phosphonation and lactonization of alkenoic acids with H‐phosphonates and H‐phosphine oxide.